Securing Pharmaceutical Supply Chains: A QR Code Approach To Counterfeit Drug Prevention - N Renushe, Hanmant; A Jadhav, Amit; Lokare, Sunita P; R. Kadam, Vrushali; I Braganza, Ashwini; Chavan, Vishal; Y Jadhav, Dhanashri; V. Patil, Vikas (Journal of Neonatal Surgery, 2025)
The worldwide pharmaceutical sector confronts a continual menace from counterfeit medications, which not only incur economic detriment but also jeopardize human lives. This study introduces a secure, scalable, and economical approach utilizing QR code technology for drug authentication at many levels of the supply chain. The suggested system encompasses QR code production at the manufacturing level, a centralized database for verification, and a mobile application for real-time scanning by customers, merchants, and distributors. The research confirms the efficacy of QR codes in identifying and combating counterfeit pharmaceuticals through a comprehensive implementation plan and pilot trial.